Social Design Thinking: an Introduction - bhekti Setyowibowo; radityo widiatmojo (University of Muhammadiyah Malang, 2023)
In today's digital age, there are many complicated social issues that need to be solved, and design thinking is certainly the most effective approach. This essay aims to elucidate the notion of design thinking, which is influenced by the demands of modern society. The major objective of design thinking is to steer clear of ideal answers and develop the best possible solutions for society. Not necessarily what is beneficial for society will be ideal. Empathy is therefore a necessary component of every social design thought process. The core building blocks of social design thinking are the five stages of information gathering, problem analysis, concept generation, prototype modeling, and critical evaluation. In order to offer the greatest potential answers, empathy must be employed at every stage. Because the main goal of social design thinking is to create sustainable, human-centered solutions.